Global Language: Status, Scope and Challenges - Bohara, Lal Bahadur (Journal of NELTA Surkhet, 2018)
The world becomes shareable, narrow, familiar, and accessible for all since we have a common language (English) despite having culture, tradition, territory and idiosyncratic variation. Because of its commonness, it is accepted as an international, global, foreign/ second language or as a lingua-franca among thousands of diverse language speakers. It becomes the global language since its form is cozily perceptible and scope is being open-ended in nature. Having its scope unlimited, the status is automatically broadened and the positional value will be transformable from fewer to more, lesser- users to frequent, foreign to second language, etc. As the status and scope of English growing up, the opportunities and challenges have been raised as well. In the forms of opportunities, people are liable to get better jobs, quality education, and international identity and so on. In contrary, challenges oppose the regular development of it which may result minimizing the status and scope sooner than later. Whatever the situation, English language is stepping forward rather than pushing back. Journal of NELTA Surkhet, Vol. 5 January, 2018